Doctoral education in social work - Anastas, Jeane W. (New York ; Oxford : Oxford University Press, 2012)
This is essential reading for anyone interested in or already working towards a social work doctorate, and for faculty and directors of schools of social work determined to understand and shape the future of doctoral education in social work.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Social sciences -- Study and teaching (Graduate) -- United States; Doctor of philosophy degree -- United States